Management of Maxillary Buccal and Palatal Impacted Canines – Case Reports (Orthodontic Journal of Nepal, 2022)
Maxillary impacted canine is one of the most common entity which a clinician encountered in day to day life. The management of impacted canines need precise diagnosis and careful application of biomechanics for optimum result. In this article 2 different case reports have been discussed which were treated with different mechanotherapy.